PELATIHAN PENGENDALIAN FAKTOR RISIKO DIABETES MELITUS PADA KADER KESEHATAN POSBINDU DI WILAYAH KERJA PUSKESMAS MARTAPURA 1 KABUPATEN BANJAR - Roswita, Ria; Nurhayati, Nurhayati; Jannah, Raudatul (UPPM Poltekkes Kemenkes Banjarmasin, 2025)
The increasing number of cases of Diabetes Mellitus from year to year and the absence of a program to control risk factors for Diabetes Mellitus independently by health cadres in Banjar Regency requires a strategy to overcome this problem. One intervention that can be done is training cadres related to Diabetes Mellitus. The purpose of this community service is to improve the knowledge and skills of cadres related to controlling risk factors for Non-Communicable Diseases, especially Diabetes Mellitus. Community service activities include education on Non-Communicable Diseases and Diabetes Mellitus as well as blood glucose examination simulations. The results of this community service are an increase in the average knowledge and skills of cadres in conducting independent blood glucose examinations.